Nevoid hypopigmentation as a manifestation of skin mosaicism - D. V. Proshutinskaya; L. V. Tekucheva (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
A case report of rare genetically specified dyschromia - nevoid hypopimentation - was described. This disease is considered as a manifestation of skin mosaicism with characteristics of clinical presentation. Literature data is given, differential diagnostics issues of this pathology are discussed.